Multi-Omics Analysis on Neurodevelopment in Preterm Neonates: A Protocol Paper. Issue 6 (November 2021) - Casavant, Sharon G.; Chen, Jie; Xu, Wanli; Lainwala, Shabnam; Matson, Adam; Chen, Ming-Hui; Starkweather, Angela; Maas, Kendra; Cong, Xiaomei S.
Abstract : Background: The gut microbiome is an important determinant of health and disease in preterm infants. Objectives: The objective of this article was to share our current protocol for other neonatal intensive care units to potentially expand their existing protocols, aiming to characterize the relationship between the intestinal microbiome and health outcomes in preterm infants. Methods: This prospective, longitudinal study planned to recruit 160 preterm infants born <32 weeks gestational age or weighing <1, 500 g and admitted to one of two Level III/IV neonatal intensive care units. During the neonatal intensive care unit period, the primary measures included events of early life pain/stress, gut microbiome, host genetic variations, and neurobehavioral assessment. During follow-up visits, gut microbiome; pain sensitivity; and medical, growth, and developmental outcomes at 4, 8–12, and 18–24 months corrected age were measured. Discussion: As of February 14, 2020, 214 preterm infants have been recruited. We hypothesize that infants who experience greater levels of pain/stress will have altered gut microbiome, including potential adverse outcomes such as necrotizing enterocolitis and host genetic variations, feeding intolerance, and/or neurodevelopmental impairments. These will differ from the intestinal microbiome of preterm infants who do not develop these adverse outcomes. To test this hypothesis, we will determine how alterations in the intestinal microbiome affect the risk of developing necrotizing enterocolitis, feeding intolerance, and neurodevelopmental impairments in preterm infants. In addition, we will examine the interaction between the intestinal microbiome and host genetics in the regulation of intestinal health and neurodevelopmental outcomes.